High Dose ACTH for Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The efficacy and plasma levels of ACTH and Cortisol were studied in 15 children with infantile spasms and hypsarrhythmia using a high dose (150 IU/M2/D ACTH) and are reported from the Department of Pediatrics, University of Alabama at Birmingham School of Medicine, and the Comprehensive Epilepsy Center, the Alabama Children's Hospital, Birmingham, AL.